MiR‐182 inhibits kidney fibrosis by regulating transforming growth factor β1/Smad3 pathway in autosomal dominant polycystic kidney disease. Issue 7 (17th February 2020) - Sun, Liping; Hu, Chaofeng; Wang, Zhen; Zhang, Xinzhou
Abstract: The aim of the present study was to investigate the molecular mechanism of miR‐182 in kidney fibrosis in polycystic kidney disease (PKD). We measured the expression of miR‐182 in kidney tissue of autosomal dominant PKD. Additionally, we investigated the relationship between miR‐182 and fibrotic protein by transfecting miR‐182 mimics and miR‐182 inhibitor into polycystic kidney cyst‐lined epithelial cells, respectively. Furthermore, we observed the interaction between transforming growth factor β1 (TGF‐β1) and miR‐182 and fibrinogen factors of cyst‐lined epithelial cells after TGF‐β1 intervention, and measured the expression of Smad2 and Smad3 protein. Results are presented as follows: (a) MiR‐182 was positively correlated with fibrosis of cyst‐lined epithelial cells; (b) TGF‐β1 could induce fibrosis of cyst‐lined epithelial cells; (c) the expression of miR‐182 had a remarkably impact on the fibrosis induced by TGF‐β1, but had little effect on the expression of TGF‐β1; (d) the expression of Smad3 protein in TGF‐β1 induce‐cyst‐lined epithelial cells was increased. TGF‐β1 and miR‐182 promoting the fibrosis of polycystic kidney cyst‐lined epithelial cells may be mediated by the TGF‐β1/Smad3 signaling pathway, of which Smad3 was an important regulator.